A Novel Approach of System-Level Data Migration and Volatile Memory Forensics for Android Applications - G.Ragu, Gosula Ramakanth Reddy, Kanadam Chandu Vardhan, Akula Abhilash (International Journal of Control and Automation, 2020)
In this research work, proposed a concept to identify the malwares occurrence while transferring the data from one device to other device. This concepts involves various steps starting with data serialization and then follows data aggregation, data collection, Big data processing, analysis, pre-processing, validation.  The entire process divided into two phases mainly. Initial phase involves transmission of data between devices and this requires the data serialization, data aggregation, data collection steps. Another phase involves identification of malware occurred during initial phase and this requires analysis, pre-processing and validation steps. The datasets are labeled with malware types initially. Then collected the dataset details from the transmission of data like source id, destination id etc. Now validate these datasets with labeled datasets to identify the malware occurred during transmission.